2011
DOI: 10.1152/ajpheart.00714.2011
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome functional insufficiency in cardiac pathogenesis

Abstract: The ubiquitin-proteasome system (UPS) is responsible for the degradation of most cellular proteins. Alterations in cardiac UPS, including changes in the degradation of regulatory proteins and proteasome functional insufficiency, are observed in many forms of heart disease and have been shown to play an important role in cardiac pathogenesis. In the past several years, remarkable progress in understanding the mechanisms that regulate UPS-mediated protein degradation has been achieved. A transgenic mouse model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 149 publications
(187 reference statements)
3
81
0
2
Order By: Relevance
“…The specificity of substrates for proteasomal degradation is primarily conferred by the E3 ubiquitin ligases. MuRF1 has been reported to be upregulated in hypertrophic and failing hearts (71). We found that the Smurf1 ubiquitin ligase expression is upregulated in PAC, the first report identifying a role of Smurf1 in cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The specificity of substrates for proteasomal degradation is primarily conferred by the E3 ubiquitin ligases. MuRF1 has been reported to be upregulated in hypertrophic and failing hearts (71). We found that the Smurf1 ubiquitin ligase expression is upregulated in PAC, the first report identifying a role of Smurf1 in cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 48%
“…UPS activity has been shown to be decreased (19,49) in human LVF; however, in rodent models of LVH and LVF, studies have shown either increased or decreased UPS activity (31,43,71). Thus the role of the UPS in LVH/LVF is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UPS function has been interrogated in a variety of in vitro and animal models and comprehensively reviewed elsewhere (40,53,66,67,78,85,91,94,100,103). Published studies most relevant for comparison to human cardiomyopathies are the 1) mouse models of desmin-related cardiomyopathies (DRCs), 2) cardiac hypertrophy models (i.e., thoracic aortic banding, isoproterenol induced), and 3) HCM-associated myosin binding protein C (MYBPC3) mutant knock in mice.…”
Section: Comparing Human Disease With Experimental Model Systemsmentioning
confidence: 99%
“…The turnover cycle becomes perturbed during cardiac injury and heart failure by factors including hypertrophic signaling (4), calcium regulation (5), and proteolytic stress (6,7), whereas increased oxidative stress compounds the reduced protein degradation capacity of the failing heart (8). Altogether, these perturbations of protein degradation and synthesis instigate a remodeling of the cardiac proteome that is believed to parallel, at the molecular level, the progressive deterioration of cardiac structure and functions (4,(8)(9)(10)(11). Hence, identifying how pathological proteome remodeling gradually manifests over time is critical to advancing our knowledge of heart diseases.…”
Section: Introductionmentioning
confidence: 99%